Implementation of the Value of Pluralism in Film Tanda Tanya (?) - Asri Yulianti*; Wawan Darmawan (Universitas Syiah Kuala, 2024)
In modern times, technology is increasingly sophisticated, one of which is the development of film at this time which has developed more rapidly. Various kinds of films as a means of entertainment on television screens, computers, laptops, and others that always convey messages in films. This study aims to describe the message contained in the film Tanda Tanya (?), this film aired in 2011 directed by Hanung Bramantyo. When this film was relased, there ware pros and cons because this film was quite sensitive. The film Tanda Tanya (?) has told the story of various tribes, religions, races, cultures, with conflicts such as berating one religionand even each others race. The method used is a descriptive qualitative approach. The results showed that the film by Hanung Bramantyo functionally has multiculturalism, pluralism, and religious values. Then there is a human relationship with God, their respective beliefs, example, and the value of jihad as the closing of the film.